The tea enthusiast's handbook : a guide to enjoying the world's best teas - Heiss, Mary Lou (Ten Speed Press, 2010)
"A guide offering concise, authoritative advice on understanding, buying, and enjoying the six classes of tea, with identification and location photography throughout"--Provided by publisher.